An imperfect world of ββ-decay nuclear data sets?. (21st May 2015) - Pritychenko, B
Abstract: The precision of double-beta ( ) decay experimental half-lives and their uncertainties is reevaluated. A complementary analysis of the decay uncertainties indicates deficiencies due to the small size of statistical samples, and incomplete collection of experimental information. Further experimental and theoretical efforts would lead towards to more precise values of -decay half-lives and nuclear matrix elements.